KEEFEKTIFAN METODE MIND MAPPING DALAM MENULIS KARANGAN (SAKUBUN) (Penelitian Eksperimen Terhadap Mahasiswa Bahasa Jepang Tingkat III Tahun Akademik 2016/2017 Universitas Riau) - Sakela, Tut Ilda Ayu; Hadriana, Hadriana; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this study was firstly emerged from the data found by the researcher that the student’s ability in writing Japanese essays (Sakubun) was still lack. The lack of ability in writing Japanese essays (Sakubun) influences the student’s Japanese language mastery level. The aim of this study is to find out the difference of student’s ability in writing Japanese essays (Sakubun) after implementing Mind Mapping method. The research method of this study was quasi experiment with one group before after or pretest and post-test group design. The sample technique used was total random sampling. The study was done by conducting pretest to know the student’s prior ability, then giving treatments in the experiment class, and the last giving post-test to know the student’s ability. Based on the data analysis, the result was sig 14,36 > 5,04. It means that H0 was rejected and Ha was accepted. Thus, it can be concluded that Mind Mapping method is effective in learning of Japanese essays (Sakubun) on the third-level students of Japanese Education Department Faculty of Teacher’s Training and Education Riau University.Keywords: Sakubun, writing skill, Mind Mapping Method